Study of Complex Formation Between Iodoquinol (IQ) and Co2+ , Mn2+, Cd2+, Pb2+ and Zn2+ Cations in Binary Aqueous / Non-aqueous Solvent Using Spectrophotometry - A. Nezhadali; H. A. Hosseini; P. Langara (E-Journal of Chemistry)
The complexation reactions between iodoquinol and Co2+, Mn2+, Cd2+, Pb2+ and Zn2+ cations were studied in different DMF/H2O binary mixtures at the ionic strength of 0.1(using NaNO3).The spectrophotometric method was used for the determination of formation constants and the stoichiometries. The stoichiometry of the complexes is established 1:1 by Job's and mole ratio methods. It was found that the stability constants of the complex formed between the ligand (IQ) and the cations in the all cases increase with increasing of the non-aqueous solvent. In the most cases the maximum formation constants between Zn2+ ion and IQ were obtained respect to the other cations.